The Role of the Visor Flap in Scalp Reconstruction: A Case Series of 21 Patients. Issue 6 (14th March 2018) - Ellis, Marco; Hwang, Lisa; Ford, Ni-Ka; Slavin, Konstantin
Abstract: BACKGROUND: Full-thickness scalp defects pose a reconstructive problem, especially in the setting of infection, chemotherapy/radiation, and underlying cranial defects. Current options include dermal matrices, skin grafts, and local flaps. Local flaps often fail, requiring subsequent microvascular free flap reconstruction. OBJECTIVE: To describe the visor flap, a novel bipedicled advancement flap design, and its role in reconstruction of scalp defects. METHODS: A retrospective review of 21 adult patients who developed scalp defects reconstructed using the visor flap from 2013 to 2017. The visor flap is a large bipedicled advancement flap design with a triangular extension at the base, which allows redistribution of a large surface area of the scalp. RESULTS: All 21 patients achieved complete and viable soft tissue coverage of the recipient site, but 19.0% developed complications unrelated to flap viability, requiring reoperation (infected bone flap, epidural hematoma, and recurrent glioblastoma with subdural abscess). Only 1 patient required conversion to free flap reconstruction due to cerebrospinal fluid leak. Etiologies included cancer (76.1%), cerebrovascular disease (19.0%), and traumatic brain injury (4.8%). Preoperative radiation (42.9%), bone/hardware exposure (57.1%), and previous craniotomy (85.7%) were widely prevalent. Defect size ranged from 3 to 50 cm 2 (mean, 16.9 cm 2 ), and flap size ranged from 90 to 500 cm 2 (mean, 222 cm 2 ). CONCLUSION: The visor flap provides an innovative solution for closure of scalp defects. This technique optimizes immediate closure of tissue compromised by infection or chemotherapy/radiation without burning bridges to more complex reconstructive options.